A single complete ultrasound investigation of the venous network for the diagnostic management of patients with a clinically suspected first episode of deep venous thrombosis of the lower limbs - Elias, Antoine; Mallard, Luc; Elias, Marie; Alquier, Catherine; Guidolin, François; Gauthier, Bruno; Viard, Alain; Mahouin, Pierre; Vinel, Anne; Boccalon, Henri (Thrombosis and Haemostasis, 2003)
In patients clinically suspected of deep-vein thrombosis (DVT) of the lower limbs, it is safe to withhold anticoagulant therapy after a negative ultrasound (US) limited to the popliteal and the femoral veins, provided that this can either be repeated or combined with other diagnostic procedures. To assess the safety of withholding anticoagulants after a single negative complete US, we performed a multicenter, prospective, cohort study including consecutive ambulatory outpatients from institutional and private practice settings, with a clinically suspected first episode of DVT. Patients fulfilling the inclusion criteria were enrolled after careful clinical assessment. A complete US examination of the proximal and the distal veins was performed according to a standardized and detailed protocol. Anticoagulant therapy was administered in patients with proximal or isolated distal DVT and withheld in those with negative results. The main outcome measure was the occurrence of objectively documented clinical thromboembolic events during a three-month follow-up after a negative US.Out of 623 patients,401 (64.4%) had a baseline negative US, were not anticoagulated and could be followed-up for three months. Two patients presented a calf DVT within three months. The incidence of venous thromboembolic events, including distal DVT, was 0.5% [95% confidence interval: 0.1-1.8]. No proximal DVT, or non-fatal or fatal pulmonary embolism occurred (incidence: 0.0% [95% confidence interval: 0.0-0.9]).In conclusion, it is safe to withhold anticoagulant therapy in patients with clinically suspected DVT after a single, negative, complete US. Integrating this method within diagnostic strategies for DVT could improve management and be more acceptable for patients and physicians.
Keywords: Ultrasonography; venous thrombosis; calf veins; prospective; cohort